EFFECT OF WORK MOTIVATION, WORK CONFLICT AND WORK ENVIRONMENT ON PERFORMANCE OF PTPN VII EMPLOYEES BANDAR LAMPUNGIN THE TIME OF THE COVID-19 PANDEMIC - Zelda, Yurike Tri; Ardansyah , Ardansyah; Defrizal, Defrizal (Program Studi Magister Manajemen, 2024)
The Covid-19 pandemic has had a major impact on global health and economy. WHO data shows that 70% of Covid-19 patients are aged 31 to 45 years. In Indonesia, the spread of the virus is high, with local transmission already occurring. The public must comply with health protocols, including companies that must also implement them.Human resource (HR) management needs to adapt to reduce crowding in the workplace. These changes affect employee performance, especially with the implementation of work from home, which can reduce performance due to motivation, conflict, and work environment. This quantitative research involved 70 employees of PT PTPN VII Bandar Lampung. The results showed F count (91.013) > F table (3.13) and a significant value of 0.000 <0.05, which means work motivation, work conflict, and work environment have a significant positive effect on employee performance. An increase in these three variables will improve employee performance.